2019
DOI: 10.1007/s42832-019-0011-0
|View full text |Cite
|
Sign up to set email alerts
|

Loss of soil microbial diversity exacerbates spread of antibiotic resistance

Abstract: Loss of biodiversity is a major threat to the ecosystem processes upon which society depends. Natural ecosystems differ in their resistance to invasion by alien species, and this resistance can depend on the diversity in the system. Little is known, however, about the barriers that microbial diversity provides against microbial invasion. The increasing prevalence of antibioticresistant bacteria is a serious threat to public health in the 21st century. We explored the consequences of the reduction in soil micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 74 publications
(91 reference statements)
5
45
1
2
Order By: Relevance
“…may favor AR spread (Chen et al, 2019a). Note that, beyond the transmission of particular AR spreading clones, AR is expected to spread in farms by the modification (eventually homogenization) of animals' microbiota.…”
Section: Highway To Antibiotic Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…may favor AR spread (Chen et al, 2019a). Note that, beyond the transmission of particular AR spreading clones, AR is expected to spread in farms by the modification (eventually homogenization) of animals' microbiota.…”
Section: Highway To Antibiotic Resistancementioning
confidence: 99%
“…The common genetic origin of these types and the process of microbiota acquisition from nearby animals in intensive farming should homogenize also their microbiomes with consequences for AR dissemination. Actually, it has been shown that the loss of microbial diversity may favor AR spread ( Chen et al, 2019a ). Note that, beyond the transmission of particular AR spreading clones, AR is expected to spread in farms by the modification (eventually homogenization) of animals’ microbiota.…”
Section: Highway To Antibiotic Resistancementioning
confidence: 99%
“…Antibiotic residues, once entered into soil through manure application, can enhance persistence and HGT of ARGs (Binh et al, 2007;Zhao et al, 2019) through plasmids and integrons (Gotz and Smalla, 1997;Smalla et al, 2000;Sengeløv et al, 2003), promoting the spread of ARB in the environment and affecting the microbial community composition (Chen et al, 2019). Although manure-derived bacteria cannot always adapt to new environments, the antimicrobials can favor the enrichment of specific bacterial taxa in soils (through positive selection) and suppress others (Ding et al, 2014).…”
Section: The Dissemination Mechanisms Of Environmental Resistomementioning
confidence: 99%
“…The increased number of resistant pathogens and commensal bacteria has been associated with the environmental spread of antibiotics and the propagation of antimicrobial resistant genes (ARGs; Levy, 1998;Witte, 1998;He et al, 2020). Furthermore, the environmental diffusion of antibiotics may lead to the change (Han et al, 2018) and loss (Chen et al, 2019) of microbial community diversity in soil (Kemper, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that microbial diversity played an important role in the resistance to microbial invasion in the natural ecosystem ( van Elsas et al, 2012 ). Some studies regarded the antibiotic resistome as a proxy for invasion and found that microbial diversity had negative correlation with the abundance of ARGs ( Chen Q. et al, 2019 ). In this study, an increase in piARG abundance was linearly associated with loss of OTU richness (observed OTUs, R 2 = 0.57, p < 0.001), OTU evenness (Pielou index, R 2 = 0.71, p < 0.001), and OTU diversity (Shannon index, R 2 = 0.72, p < 0.001).…”
Section: Resultsmentioning
confidence: 99%